2008
DOI: 10.1021/bi701530w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trehalose on W7FW14F Apomyoglobin and Insulin Fibrillization:  New Insight into Inhibition Activity

Abstract: Trehalose, a disaccharide present in many nonmammalian species, protects cells against various environmental stresses. Trehalose has recently been shown to decrease aggregate formation and toxicity in cell models and to alleviate amyloid-induced diseases. The aim of our study was to use two amyloid-forming proteins, i.e., W7FW14F apomyoglobin and insulin, as model systems to elucidate the molecular mechanism by which trehalose affects the amyloid aggregation process and to investigate further its therapeutic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 49 publications
3
53
2
1
Order By: Relevance
“…In the same study, the effect of ectoines was shown on prevention of Aȕ 1-42 -induced cell toxicity, with ectoine being more effective [214]. On the other hand, a recent study aimed at elucidating mechanism of amyloid inhibition by trehalose involving two model proteins indicated while delay/inhibition of fibrillation are obvious, more toxic oligomeric species may be formed during the process [215]. This again highlighted the need for more detailed studies on small molecules that inhibit amyloid fibril formation.…”
Section: Small Stress Moleculesmentioning
confidence: 94%
“…In the same study, the effect of ectoines was shown on prevention of Aȕ 1-42 -induced cell toxicity, with ectoine being more effective [214]. On the other hand, a recent study aimed at elucidating mechanism of amyloid inhibition by trehalose involving two model proteins indicated while delay/inhibition of fibrillation are obvious, more toxic oligomeric species may be formed during the process [215]. This again highlighted the need for more detailed studies on small molecules that inhibit amyloid fibril formation.…”
Section: Small Stress Moleculesmentioning
confidence: 94%
“…The effects is dose-dependent and depends on the protein. Also the lag phase of insuline was increased in the presence of trehalose [207].…”
Section: Protein Oligomerization Polymerization and Amyloid Aggregationmentioning
confidence: 96%
“…Additional examples include aggregation of rhGCSF at 37 ° C at pH 7 158 and W7FW14F apomyoglobin at pH 7.0 at room temperature. 120 Other proteins are prone to aggregation at a pH slightly below or above the neutral condition, including fi refl y luciferase at pH 5.5 at 30 ° C, 80 a botulinum neurotoxin (50 kD) at pH 8 at 50 ° C, 159 an Fc fusion protein at pH 3.6 at room temperature, 160 a mAb and ovalbumin at pH 4.0 at 37 ° C, 40 and a mouse mAb (mIgG1) at pH 3.9 at or above room temperature. 161 Protein aggregation caused by pH changes can be simply an effect of altered charge -charge interactions and/or pH -induced protein destabilization/ partial unfolding.…”
Section: Protein Aggregation Under Neutral and Moderate Acidic/basicmentioning
confidence: 99%
“…183 These sugars/polyols do not seem to work on all stages of the aggregation process. Vilasi et al 120 found that trehalose (50 -600 mM) did not suppress the early phase of the aggregation process (formation of prefi brillar oligomeric structures) of a apomyoglobin analogue but did inhibit the formation of fi brils from early aggregates in a dose -dependent manner. Because of this effect, tre- halose seems to maintain the aggregates in a nonfi brillar, highly cytotoxic state.…”
Section: Small Neutral Additivesmentioning
confidence: 99%